A Study of Vernacular Narratives in Modern and Contemporary Chinese Literature - Wang, Kezhou (Transactions on Social Science, Education and Humanities Research, 2024)
Through a comprehensive discussion of the historical evolution, themes and imagery, characterisation, language and style, and contemporary values and influences of vernacular narratives in modern and contemporary Chinese literature, this paper reveals the unique manifestations of vernacular narratives and their profound connotations at different historical stages. With their unique perspectives and profound social insights, vernacular narratives depict the life of rural China, reflecting the realities of social change and cultural inheritance. Writers such as Lu Xun, Shen Congwen, and Mo Yan, through their respective classic works, not only enriched the themes and techniques of literary creation, but also provided readers with an important window to understand rural life and social reality. In contemporary times, vernacular narratives continue to play an important role by focusing on rural issues and preserving cultural memories, arousing people’s identification with and concern for rural culture. The purpose of this paper is to reveal the unique position and significance of vernacular narratives in contemporary Chinese literature and to explore their inspiration and contribution to contemporary literary creation through a multi-angle analysis of vernacular narratives.